Program Cell Death Receptor-1-Mediated Invariant Natural Killer T-Cell Control of Peritoneal Macrophage Modulates Survival in Neonatal Sepsis - Fallon, Eleanor A.; Chun, Tristen T.; Young, Whitney A.; Gray, Chyna; Ayala, Alfred; Heffernan, Daithi S. (Frontiers in Immunology, 2017)
We have shown that iNKT cells mediate sepsis induced end-organ changes and immune responses, including macrophage bacterial phagocytosis, a finding regulated by the check point protein Program Cell Death Receptor-1 (PD-1). Further, PD-1 mediates mortality in both adult and neonatal murine sepsis as well as in surgical patients. Given our previous findings, we hypothesize that iNKT-cells will also modulate neonatal sepsis survival, and that this effect is regulated in part through PD-1. We utilized a polymicrobial intra-peritoneal cecal slurry (CS) sepsis model in either, wild type (WT), iNKT-/- or PD-1-/- 5-7 day old neonatal pups. Typically, tissues were harvested at 24 hrs for various bioassays/histology and in some cases survival was assessed for up to 7 days. Interestingly, similar to what we recently reported for PD1-/- mice following CS, iNKT-/- deficient animals exhibit a markedly improved survival vs. WT. Histologically, minor alterations in liver architectural which were noted in WT pups were attenuated in both iNKT-/- and PD-1-/- pups. Following CS, PECAM-1 expression was unchanged in the WT pups, but increased in both iNKT-/- and PD1-/- pups. In WT, following CS the emergence of a Ly6Clow subpopulation was noted among the influxed peritoneal macrophage population. Conversely, within iNKT-/- pups, there were fewer peritoneal macrophages and a greater percentage of Ly6Chigh macrophages. We show not only a key role for iNKT cells in affecting end organ damage as well as alterations in phagocytes phenotypes in neonatal sepsis, but that this iNKT cell mediated effect is driven by the central checkpoint protein PD-1.